Objectivos e aspectos estratégicos da invasão se Soult - Silva, Francisco Ribeiro da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Although the generally called French invasions should be looked from a more general perspective, whether considering the Portuguese or the European history, there is no doubt that the invasion commanded by Soult in 1809 was the most significant offensive of the Napoleonic military in the history of Porto and northern Portugal. Concurrently with the geographical study of the invasion and based on the memoirs of M. Le Noble, this paper suggests an interpretation of the duke of Dalmatia’s objectives, as well as of the exceptional strategic skills revealed in the field of operations.